Complementary Use of Various Types of Anthropogenic Habitats by Scolia hirta (Hymenoptera: Scoliidae) and Scolia sexmaculata. Issue 6 (6th November 2019) - Twerd, Lucyna; Sobieraj-Betlińska, Anna; Banaszak, Józef
Abstract: Scolia hirta (Schrank) and Scolia sexmaculata (O.F. Müller) are Palearctic, parasitic Aculeata inhabiting forests and forest steppes. At present, the abundance and dispersal of these species are increasing considerably in Poland and other European countries, allowing observation of their possible habitat preferences. The analysis of the preferences of S . hirta and S . sexmaculata was conducted in Northern and North-Eastern Poland based on the evaluation of their occurrence in six types of habitats: (A) psammophilous and xerothermic grasslands, (B) old fields, (C) city outskirts, (D) sites in housing/industrial zones, (E) sand quarries, (F) post-industrial wastelands, and in a total of three types of landscape: 1) semi-natural, 2) urban, and 3) industrial. We demonstrated that the habitat most frequently colonized by S. hirta is post-industrial wastelands, while S. sexmaculata were most often sampled in old fields, with the frequency of 100% and 94.11%, respectively. At the same time, the abundance of the species in these habitats was also the highest, with a mean of 8.00 and 10.88 individuals, respectively. Moreover, S. hirta was relatively frequently found in the urban landscape (67% in city outskirts and 88.23% in the housing/industrial zones), while S. sexmaculata colonized these areas to a considerably low degree (25% in city outskirts and 29.41% in the housing/industrial zones). We also established that the occurrence of the species was affected by the forest cover in the closest vicinity of the study sites, which significantly modified the habitat preference of the species analyzed.